PENERAPAN MODEL MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN SISWA - NIKE IRI WANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The writing of this Best Practice report was motivated by the author's observations during the learning process in the classroom, which showed the low activeness of students in participating in learning activities in class. The application of the Make A Match learning model aims to (1) Students can know and apply the steps of the Make A Match learning model. (2) Can increase student activity in participating in the process of teaching and learning history in the classroom on the Basic Competence of the Maritime Kingdoms of the Hindu-Buddhist Period in Indonesia in class XI IPS SMA N 1 Semester 1 Session of the 2019/2020 academic year. The steps in the Make A Match method include: The teacher arranges the children's room and seating, the teacher provides direction on the material being studied and the rules of the game in learning Make A Match, students take turns taking yellow question cards and pink answer cards , students interact with each other and discuss to match the question cards and answer cards. Students who successfully match pairs of question cards and answer cards are given value points, the teacher together with students concludes the material and learning Make A Match. The impact of the use of the Make A Match method, among others: students learn to enjoy and have fun, the realization of collaboration between students dynamically, the material presented to students is more relevant, effective and trains student discipline to appreciate time in learning and can increase student learning activities both cognitively and affectively. ABSTRAKPenulisan laporan Best Practice ini dilatarbelakangi oleh pengamatan penulis selama proses pembelajaran di kelas, yang menunjukan rendahnya keaktifan siswa dalam mengikuti kegiatan pembelajaran di kelas. Penerapan model pembelajaran Make A Match bertujuan untuk (1) Siswa dapat mengetahui dan menerapkan langkah-langkah model pembelajan Make A Match. (2) Dapat meningkatkan keaktifan siswa dalam mengikuti proses kegaiatan belajar mengajar sejarah di kelas pada Kompetensi Dasar Kerajaan-Kerajaan Maritim Masa Hindhu-Budha di Indonesia kelas XI IPS SMA N 1 Kesesi Semester 1 Tahun Pelajaran 2019/2020. Langkah-langkah dalam metode Make A Match meliputi : Guru menata ruang dan tempat duduk anak, Guru memberikan pengarahan tentang materi yang dipelajari dan aturan main dalam pembelajaran Make A Match, Siswa secara bergiliran mengambil kartu soal yang berwarna kuning dan kartu jawaban yang berwarna merah muda, siswa saling berinteraksi dan berdiskusi untuk mencocokan antara kartu soal dan kartu jawaban. Siswa yang berhasil mencocokan pasangan kartu soal dan kartu jawaban diberi poin nilai, guru bersama – sama siswa menyimpulkan materi dan pembelajaran Make A Match. Dampak dari penggunaan metode Make A Match anatara lain: siswa belajar menjadi enjoy dan menyenangkan, terwujudnya kerja sama antar siswa secara dinamis, materi yang disampaikan kepada siswa lebih mengena, efektif dan melatih kedisplinan siswa untuk menghargai waktu dalam belajar serta dapat meningkatkan keaktifan belajar siswa baik secara kognitif maupun afektif.